Variation and Dynamics of Soil Nematode Communities in Greenhouses with Different Continuous Cropping Periods - Xueliang Tian; Xiaoman Zhao; Zhenchuan Mao; Bingyan Xie (Horticultural Plant Journal, 2020)
Continuous cropping in greenhouses can result in root-knot nematode outbreaks resulting from imbalances in the soil nematode community. However, the changes in soil nematode communities in greenhouses with continuous crop production are unclear. We compared soil nematode communities in greenhouses after 2 years (2-yr) and 10 years (10-yr) of continuous crop production by 18S rDNA high-throughput sequencing. Compared with the 2-yr greenhouse, soil in the 10-yr greenhouse showed acidification, nutrient accumulation and salinization. Bacterial-feeding nematodes (BF) were dominant in the 2-yr greenhouse over the whole growing season, but plant-parasitic nematodes (PP) were the dominant group in the 10-yr greenhouse during the late growing season. Meloidogyne gradually became the dominant group and had a relative abundance of 70.9% (maximum) in the 10-yr greenhouse. Rhabditidae, with relative abundance ranging from 99.8% to 26.8%, was the predominant group in the 2-year greenhouse. For β-diversity, hierarchical clustering analysis, unweighted UniFrac principal component analysis (PCA) and principal co-ordinates analysis (PCoA) all revealed that soil nematode communities in the two types of greenhouses were significantly different. Redundancy analysis (RDA) showed that soil nematode communities in the 10-yr greenhouse were related to high soil organic material, total nitrogen, electrical conductivity and disease index of root-knot nematodes. Fisher's exact test and Pearson's correlation coefficients revealed that Meloidogyne contributed to the main differences in soil nematode communities between the two types of greenhouses. Population dynamics of Meloidogyne were divided into dormant phase, low-level increasing phase and exponential phase during the whole season. The soil nematode communities within the 2-yr and 10-yr greenhouses had significant variation and different dynamics. This work contributes to a deeper understanding of changes in the soil nematode community in greenhouses with different continuous cropping duration.